Analysis of biomedical data with SPSS - Foo, Yu Xi. (2010)
Dynamic Contrast-enhanced Magnetic Resonance Imaging (DCE-MRI) is used to monitor therapeutic response and predict outcomes in the study of cancer treatment. Clinical trial data collected from this process will be used for analysis in this report. This report serves as a guide to the utilization of the SPSS software in statistical testing. Real-time clinical trial data are analyzed with regards to their correlation with one another. Pre-correlation testing is necessary to determine the right technique to use and the analysis of the significance of the data will also play a big role in the interpretation of the data and the conclusion of the test. Controlling unintended correlation effect of other variables proves to be an important technique in understanding the true and unique relationship between variables. Correlation results may not be accurate and therefore, there is also a need to look into the accuracy of correlation.